(untitled) (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
The project LODZ (Linked Open Data Zurich) adopts an experimental approach to merge data and develop a semantic web infrastructure to enable its discovery. For this purpose, three institutions in the field of art and design provided their metadata. The project cycle followed six steps: team building, gathering and cleaning of the original data, modelling, transforming, interlinking and exploration of the Linked Data set. The resulting pilot application offers innovative and attractive features based on the capability of the Linked Data, with the aim to provide a better user experience. The major challenge of this project was the creation of links between the internal datasets, and with external sources. An important lesson learnt is therefore to focus more on the interoperability of data at the time of cataloguing in the original databases, for example by integrating external identifiers rather than just terms in the form of strings.